Avaliação da tenacidade à fratura pela técnica de CTOD em juntas soldadas do aço 22MnB5+NbMo - Soccol, Lucas (2022)
Hot stamping is a metal forming process, where the material is heated and during the forming procedure it undergoes an accelerated cooling, performing quenching. In an attempt to improve the process, a new steel alloy was developed, adding Nb and Mo in the steel to boron 22MnB5. In this context, the objective of the present study was to evaluate the fracture toughness by CTOD in the different regions of the joints welded by the GMAW process of 22MnB5+NbMo steel of great thickness after hot stamping. Initially, the specimens were hot stamped, austenitized at 950ºC for 5min and cooled at a rate of 27ºC/s, followed by robotic MAG welding, using filler metal ER110S-G. To quantify the mechanical properties, tensile, hardness and fracture toughness tests were performed by CTOD. The CTOD tests were performed on SE(B) specimens, with bending stress at three points, under a frequency of 10Hz, ΔK of 25.20 MPa√ and fatigue ratio R=0.1. Pre-crack monitoring was carried out using clip-gage until reaching an a/W ratio of 0.55. Fracture analyzes were performed by scanning electron microscopy. In conclusion, it was identified that the temperature from the welding process had a significant influence on the reduction of hardness, mechanical strength and microstructural changes, in addition to providing an increase in fracture toughness of the white region and the HAZ, however, the welding did not negatively influence the structural integrity of the welded joints, considering that the lowest values of CTOD were obtained in the hot stamped MB. Furthermore, a gain in fracture toughness of approximately 180% was identified in 22MnB5+NbMo Steel when compared to 22MnB5 Steel without the presence of Nb and Mo, both hot stamped.